NeemAzal®-T/S Can Trigger Early Defense Responses in Susceptible Sunflower Seedlings Inoculated with Plasmopara halstedii: An Approach Based on the Enzymatic ROS Scavenging System - Oliveira, Kevein Ruas [UNESP]; Körösi, Katalin; Barna, Balazs; Bán, Rita; Bennett, Sarita Jane; Gratão, Priscila Lupino [UNESP] (MDPI, 2025)
Downy mildew, caused by Plasmopara halstedii, is a major threat to sunflower production worldwide, leading to severe yield losses. Since resistance in sunflower hybrids can be easily broken by the pathogen, it is important to find alternative and sustainable control methods against this disease. This study investigated the potential use of NeemAzal®-T/S (a neem-based biopesticide formulation) to induce antioxidant defense responses in sunflower seedlings inoculated with P. halstedii (pathotype 704). Its effects, alone, or in combination with a reduced dose of Mefenoxam, were evaluated under controlled conditions. Plant height, sporulation, antioxidant enzyme activities (SOD, CAT, APX, POX, and PPO), lipid peroxidation (MDA), and hydrogen peroxide (H2O2) contents were measured. Our results indicate that the antioxidant responses of seedlings varied according to the treatment. MDA levels decreased even when NeemAzal®-T/S was applied alone, while H2O2 production only decreased when both treatments were applied combined. Overall, NeemAzal®-T/S can be a valuable alternative strategy to help control sunflower downy mildew, since it reduced sporulation and MDA content, and increased APX, POX, and PPO activities even at a later stage of infection in susceptible seedlings. These findings indicate that NeemAzal®-T/S can activate defense mechanisms associated with oxidative stress reduction in sunflower, offering a promising strategy to help manage downy mildew in a more sustainable manner.